42.2k views
3 votes
-1/5c+2+c=1/5(10c-20)

1 Answer

1 vote

Let's solve your equation step-by-step.

(− 1 /5 )(c)+2+c= 1 /5 (10c−20)

Step 1: Simplify both sides of the equation.

(− 1 /5 )(c)+2+c= 1 /5 (10c−20)

(− 1 /5 )(c)+2+c=( 1 /5 )(10c)+( 1 /5 )(−20) (Distribute)

−1 /5 c+2+c=2c+−4

( −1 /5 c+c)+(2)=2c−4 (Combine Like Terms)

4 /5 c+2=2c−4

4 /5 c+2=2c−4

Step 2: Subtract 2c from both sides.

4/5 c+2−2c=2c−4−2c

−6 /5 c+2=−4

Step 3: Subtract 2 from both sides.

−6 /5 c+2−2=−4−2

−6 /5 c=−6

Step 4: Multiply both sides by 5/(-6).

( 5 /−6 )*( −6 /5 c)=( 5 /−6 )*(−6)

c=5

Answer:

c=5

User Davur
by
5.8k points